(untitled) (European Journal of Marketing and Economics, 2023)
Family firms are considered the world’s most predominant form of business organisation. Notwithstanding the fact that there is a lack of consensus with regards to their definition, on recognise that family firms are different from non-family businesses due to their specific relations at three levels, namely ownership, business and family. It would appear that the family influences, shapes and conditions both the firm and its continuity, mainly through the intergenerational management succession, its planning and effectiveness. According to a recent research focused on the entrepreneurial succession in Portugal (AEP, 2011), 50 percent of family businesses are not passed on to the second generation, and only 20 percent reach the third generation. Also, taking into account the main results from the project “Roadmap for Portuguese Family Businesses” (NORTE2020/FEDER), the empirical findings have proved that the business succession planning has been identified as one of the most challenging steps in the life of the family firm, which demands for appropriate analysis. In fact, resistance to succession, relationship founder/ successor, planning of succession, type of organisational culture, among others, explain how executive succession is one of the most important and hardest tasks in organisational life. In this article, we aim to discuss the main management challenges of a family business, particularly the importance of succession preparation and the role of the family in the socialisation of the second (third or subsequent) generation. Based on an online survey (N 1148) and on in-depth interviews conducted to founder/ manager/ owner (N 23), we will seek to point out major challenges faced by the Portuguese family business, as far as this matter is concerned.